2010
DOI: 10.1111/j.1539-6924.2010.01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Risk Assessment of Vibrio parahaemolyticus in Finfish: A Model of Raw Horse Mackerel Consumption in Japan

Abstract: The aim of this study was to evaluate the effects of implemented control measures to reduce illness induced by Vibrio parahaemolyticus (V. parahaemolyticus) in horse mackerel (Trachurus japonicus), seafood that is commonly consumed raw in Japan. On the basis of currently available experimental and survey data, we constructed a quantitative risk model of V. parahaemolyticus in horse mackerel from harvest to consumption. In particular, the following factors were evaluated: bacterial growth at all stages, effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 6 publications
(15 reference statements)
0
15
1
1
Order By: Relevance
“…Previous studies suggested the prime quality of shrimps can be retained for 8 days under low temperatures . A beta‐Poisson model was chosen to describe the dose–response relationship between the probability of illness and V. parahaemolyticus : Pi=11+Dγβα …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggested the prime quality of shrimps can be retained for 8 days under low temperatures . A beta‐Poisson model was chosen to describe the dose–response relationship between the probability of illness and V. parahaemolyticus : Pi=11+Dγβα …”
Section: Methodsmentioning
confidence: 99%
“…From farm to fork, prawn commonly undergoes a variation of temperature from ambient to freezing ranges. Temperature is a main factor influencing the pathogenic behavior in seafood such as prawn (Ying & Xi-bin, 2006), oyster (McLaughlin et al, 2005;Yoon et al, 2008;Zimmerman et al, 2007), salmon (Yang et al, 2009), fish (Yang et al, 2008), horse mackerel (Iwahori et al, 2010), Chesapeake Bay oyster (Kaneko & Colwell, 1973) and mussel (Julie et al, 2010). However, the studies of prawn had not included the effect of temperature in a wide range, especially in high ambient and low freezing ranges.…”
Section: Introductionmentioning
confidence: 96%
“…Vibrio parahaemolyticus is a gram‐negative, halophilic, mesophilic, rod‐shaped bacterium that is widely distributed in marine environment and seafood, and has been recognized as one of the most common causes of the seafood‐borne outbreaks in the United States, China, and many other Asian countries, including Japan and India (Chen et al., ; Iwahori et al., ; Wu, Wen, Ma, Ma, & Chen, ). In China, the consumer demand for shrimp has steadily increased.…”
Section: Introductionmentioning
confidence: 99%